Village Sovereignty in Dispute Resolution after Law No 6 of 2014 concerning Village - Isdiyanto, Ilham Yuli (Jurnal Media Hukum, 2019)
The research was conducted in order to strengthen the position of the village as a form of social control institution in solving problems that is present in the village setting which began to disappear since the independence era. A descriptive-qualitative approach with a historical-normative method is used to find the concept of the village sovereignty, obtained from studies of primary and secondary legal data. The research aims to get a historical picture as a conceptual reflection and judicial basis for developing and legitimizing the village as the place for resolving disputes among the populace. Since the monarchy until the colonial era, the village was given the authority to solve the problems of its people independently, this authority is severed after entering the independence era. The government finally began to realize the importance of village as autonomous and independent through Law No. 6 of 2014 concerning Villages and strengthened by Supreme Court Regulation; PERMA No. 1 of 2016 concerning the Mediation Process in the Court. Through the Regulation, the village head now has the authority to resolve the problems among its populace and create agreements regarding it. Hence, support from the government is needed to the respective village heads and the chosen delegates through regulation and mediation training